Islamic Education Leadership Management In Independent Learning Educational Curriculum Quality : Challenge Analysis And Solutions - Rini Werdiningsih; Ali Yusron; Sumarni Rumfot; Madaling Madaling; Muhammad Hafiz (At-Tarbiyat, 2023)
This study examines the leadership management of Islamic education in the quality of education in the Free Learning Curriculum in terms of the analysis of challenges and solutions. The research used in this study is a qualitative research type of descriptive research. Primary data sources are school principals, teachers at SDN 01 Kota Bangun and secondary data from books, journals and websites related to the research title. Data collection techniques using observation, interviews and documentation. Data analysis using data reduction, triangulation, member checks and making data conclusions. The results of this study indicate that school leadership identifies and validates the pathways through which leadership impacts key teaching and learning processes in schools. In addition, it was found that the use of digital technology provides new challenges in the world of education today. Innovation is needed especially for school principals as leaders in the school sector to realize the various aspirations of the nation's education. The leadership model most relevant to educational issues. Based on the results of leadership management research by school principals acculturated with a humanist approach to making technological innovation programs with an independent learning curriculum. One aspect that is realized is creating teacher human resources with high character and innovation in the digital era.